Peer Victimization and Subjective Well-Being Among Chinese Adolescents: Moderated Mediation by Forgiveness and Self-Esteem - Liu, Jiaoyu (Journal of interpersonal violence, 2023)
Considerable developmental research has shown an association between peer victimization and subjective well-being among adolescents. However, the mediating processes and protective factors that constrain this association are less understood. To fill these gaps, we investigated whether self-esteem mediates the association between peer victimization and subjective well-being and whether forgiveness moderates the direct and indirect associations of peer victimization with adolescents’ subjective well-being via self-esteem. A large sample of 2,758 adolescents (Mage = 13.53 years, SD = 1.06) from 10 middle schools in China participated in this study. Participants provided data on demographic variables, peer victimization, self-esteem, forgiveness, and subjective well-being by answering anonymous questionnaires. After controlling for demographic covariates, we found that self-esteem mediated the relationship between peer victimization and subjective well-being. Furthermore, as a protective factor, forgiveness moderated the relationship between peer victimization and self-esteem. Consistent with the protective-reactive model, when adolescents experienced more peer victimization, those with higher forgiveness levels exhibited a greater decline in self-esteem, and low self-esteem was then associated with decreased subjective well-being. These findings demonstrate the utility of examining both mediating and moderating factors in this relationship and highlight the negative impact of peer victimization on adolescent self-worth and the limited role of forgiveness as a protective factor.